Asuhan Senam Hamil Untuk Menurunkan Intensitas Nyeri Punggung Bagian Bawah - Levi Almatia Putri Pratama; Sri Maryati Sri Maryati (Ide Insan Kreatif, 2024)
ABSTRACT The incidence of discomfort felt by pregnant women is still high, one of them is lower back paint with a prevalence in Indonesian of 70% and in PKM “C” of 70%. The negative impact of lower back pain is that it can reduce the quality of life of pregnant women due to disruption of daily physical activities. Treatment using pharmacological and non-pharmacological methods can minimize the pain experienced by pregnant women. One non-pharmacological therapy is pregnancy exercise. The method in this research is a case study by assessing subjective, objective data and interviews. Case study conducted on Mrs.